Radiation-induced vaginal stenosis: current perspectives - Morris L; Do V; Chard J; Brand AH (Dove Medical Press, 2017)
Lucinda Morris,1 Viet Do,1 Jennifer Chard,1 Alison H Brand2,31Crown Princess Mary Cancer Centre Westmead, Radiation Oncology Network, Westmead, 2Discipline of Obstetrics, Gynaecology and Neonatology, Westmead Clinical School, University of Sydney, Camperdown, 3Department of Gynaecological Oncology, Westmead Hospital, Westmead, NSW, AustraliaAbstract: Treatment of gynecological cancer commonly involves pelvic radiation therapy (RT) and/or brachytherapy. A commonly observed side effect of such treatment is radiation-induced vaginal stenosis (VS). This review analyzed the incidence, pathogenesis, clinical manifestation(s) and assessment and grading of radiation-induced VS. In addition, risk factors, prevention and treatment options and follow-up schedules are also discussed. The limited available literature on many of these aspects suggests that additional studies are required to more precisely determine the best management strategy of this prevalent group after RT.Keywords: gynecological cancer, radiation therapy, vaginal stenosis, brachytherapy, vaginal dilators